Associations of Cigarette Smoking With Subclinical Inflammation and Atherosclerosis: ELSA‐Brasil (The Brazilian Longitudinal Study of Adult Health) - Kianoush, Sina; Yakoob, Mohammad Yawar; Al‐Rifai, Mahmoud; DeFilippis, Andrew P.; Bittencourt, Marcio S.; Duncan, Bruce B.; Bensenor, Isabela M.; Bhatnagar, Aruni; Lotufo, Paulo A.; Blaha, Michael J. (Journal of the American Heart Association, 2017)
There is a need to identify sensitive biomarkers of early tobacco-related cardiovascular disease. We examined the association of smoking status, burden, time since quitting, and intensity, with markers of inflammation and subclinical atherosclerosis. We studied 14 103 participants without clinical cardiovascular disease in ELSA-Brasil (Brazilian Longitudinal Study of Adult Health). We evaluated baseline cross-sectional associations between smoking parameters and inflammation (high-sensitivity C-reactive protein [hsCRP]) and measures of subclinical atherosclerosis (carotid intima-media thickness, ankle-brachial index, and coronary artery calcium [CAC]). The cohort included 1844 current smokers, 4121 former smokers, and 8138 never smokers. Mean age was 51.7±8.9 years; 44.8% were male. After multivariable adjustment, compared with never smokers, current smokers had significantly higher levels of hsCRP (β=0.24, 0.19-0.29 mg/L; <0.001) and carotid intima-media thickness (β=0.03, 0.02-0.04 mm; <0.001) and odds of ankle-brachial index ≤1.0 (odds ratio: 2.52; 95% confidence interval, 2.06-3.08; <0.001) and CAC >0 (odds ratio: 1.83; 95% confidence interval, 1.46-2.30; <0.001). Among former and current smokers, pack-years of smoking (burden) were significantly associated with hsCRP ( <0.001 and =0.006, respectively) and CAC ( <0.001 and =0.002, respectively). Among former smokers, hsCRP and carotid intima-media thickness levels and odds of ankle-brachial index ≤1.0 and CAC >0 were lower with increasing time since quitting ( <0.01). Among current smokers, number of cigarettes per day (intensity) was positively associated with hsCRP ( <0.001) and CAC >0 ( =0.03) after adjusting for duration of smoking. Strong associations were observed between smoking status, burden, and intensity with inflammation (hsCRP) and subclinical atherosclerosis (carotid intima-media thickness, ankle-brachial index, CAC). These markers of early cardiovascular disease injury may be used for the further study and regulation of traditional and novel tobacco products.